Komunikace - veřejná správa a občan(obecné závěry) - Brychtová, Šárka; Duplinský, Josef (Univerzita Pardubice, 2004)
The article "Participation of citizens on public administration in municipal level (paper to this theme on basic of empirical search)" presents closing synthesis and at the same time the nuse over results of the search of "Communication in public administration". The authors tried to describe these problems by briefly way and perhaps too with mild view. This problem was worked and published in Scientific Papers of the University of Pardubice in 2003 and in Public Administration in 2004 in detailed version and in the full wording.
Keywords: Komunikační strategie; občanská společnost; veřejná správa